Haemophagocytic syndrome and histiocytic necrotising lymphadenitis (Kikuchi's disease). Issue 8 (1st August 2000) - Mahadeva, U; Allport, T; Bain, B; Chan, W K
Abstract : A young boy presented with a rash, fever, and cervical lymphadenopathy, originally thought to be caused by tuberculosis. A lymph node biopsy showed the features of Kikuchi's disease, with necrosis and histiocytic infiltration without neutrophils. No evidence of tuberculosis was found on staining, culture, or the polymerase chain reaction. Bone marrow biopsy revealed prominent haemophagocytosis, and a diagnosis of haemophagocytic syndrome was reached. The aetiology of haemophagocytic syndrome, and its association with Kikuchi's lymphadenitis, is discussed.